O jogo na arquibancada: o setor alvinegro e as performances do torcer no contexto do futebol espetacularizado - Morais, Diego Batista de (2015)
This work investigates how to set appointments among supporters and fans and what implications can be seen in their performances in the context of spectacularized soccer. Here, it is understood that there is a game going on in the soccer bleachers, where the performances of fans and supporters are communicated to the audience, but also transmitted to an indefinite number of people watching, for example, on television. This game is a cultural phenomenon (is maintained even after processing) and acts parallel to what is played on the field (the soccer match itself), containing similar agonistic elements. Disputes usually circulate around the various ways of being in the game. These differences are expressed in the ways cheer, sing, vibrate, which use the stadium, the places they choose to attend soccer matches, among other ways. This research is anthropological, mainly using up of participant observation and interviews with members of a crowd of “Ceara Sporting Club” called “Setor Alvinegro”. This crowd is named as "torcida de alento" a new meaning from the conduction another habitus to fans, as opposed to a model understood by them as traditional supporters. The approach of the game occurs in face to face interactions, usually in stages, based on a phenomenological perspective, from Schutz, and interactionism, from the influences of Simmel and Goffman. In this game, the various supporters (here understood as teams) lay pipelines (ideologies) to be performing during interactions, which creates conditions for disputes by recognition, space and power. In the meantime these disputes and attempts to appointments, there is a latent moral supporter, as thread that also allows the event of a competition around the universalization of a way of playing the game, as if there were a "real" way to demonstrate your passion for a soccer team.